Peran Guru sebagai Penuntun dalam Mengembangkan Sikap Tanggung Jawab Murid: Sebuah Kajian Epistemologi Kristen [The Role of Teachers as Guides in Developing Students' Attitude of Responsibility: A Study of Christian Epistemology] - Ferren Ferren; Bertha Natalina Silitonga (Universitas Pelita Harapan, 2024)
Responsibility is an attitude needed to shape a person in making decisions and acting. Every student is expected to be responsible for themselves, the community, and the environment. Yet, in reality a lack of responsibility still occur among students. For example, KPAI data in 2020 showed 480 students were victims of bullying. This shows the need for the role of Christian teacher to guide students to an attitude of responsibility according to Christian ethics. Therefore, the purpose of this study are to explain the significance of the teacher's role in the formation of student responsibility and to explain the role of the teacher as a guide to develop the attitude of responsibility of the students. The method used is the literature review method. The results shows that a Christian teacher as a role model is needed for students transformation. Christian teacher is a God's coworker to introduce God and bring students in restoring relationships with God. For the next research it is suggested to explore deeper about the role of Christian teacher in character education, especially the responsibility and implementation of character education to develop students' responsiblity.BAHASA INDONESIA ABSTRACT: Tanggung jawab merupakan sikap yang diperlukan untuk membentuk seseorang dalam mengambil keputusan dan bertindak. Setiap mahasiswa diharapkan dapat bertanggung jawab terhadap diri sendiri, masyarakat, dan lingkungannya. Namun, pada kenyataannya sikap tanggung jawab masih banyak terjadi di kalangan pelajar. Sebagai contoh, data KPAI pada tahun 2020 menunjukkan 480 siswa menjadi korban perundungan. Hal ini menunjukkan perlunya peran guru agama Kristen untuk membimbing siswa memiliki sikap tanggung jawab sesuai dengan etika Kristen. Oleh karena itu, tujuan dari penelitian ini adalah untuk menjelaskan pentingnya peran guru dalam pembentukan sikap tanggung jawab siswa dan menjelaskan peran guru sebagai pembimbing untuk mengembangkan sikap tanggung jawab siswa. Metode yang digunakan adalah metode tinjauan pustaka. Hasil penelitian menunjukkan bahwa guru Kristen sebagai teladan sangat dibutuhkan dalam proses transformasi siswa. Guru Kristen adalah rekan sekerja Tuhan untuk memperkenalkan Tuhan dan membawa siswa dalam memulihkan hubungan dengan Tuhan. Untuk penelitian selanjutnya disarankan untuk menggali lebih dalam mengenai peran guru Kristen dalam pendidikan karakter, khususnya tanggung jawab dan implementasi pendidikan karakter untuk mengembangkan tanggung jawab siswa.